FRI0160 Disease activity and autoantibody positivity are increased in rheumatoid arthritis patients with co-existent bronchiectasis. (23rd January 2014) - Perry, L.; Hutchinson, D.; De-Soyza, A.; Eggleton, P.; Kelly, C.
Abstract : Background: Previous studies have found no difference in RA disease severity measures (early morning stiffness, swollen joint count, HAQ, radiological findings) or auto-antibodies (rheumatoid factor) between patients with Bronchiectasis and Rheumatoid Arthritis (BRRA) and those with RA alone 1, 2 . Current validated RA disease activity measures such as DAS28-CRP and modern autoantibodies, anti-cyclic citrullinated peptide antibodies (ACPA) have not been compared between these groups. Objectives: To determine if there is a difference in RA disease activity/severity and autoantibody status between patients with Bronchiectasis and Rheumatoid Arthritis and those with RA alone. Methods: Screening clinics at 3 NHS Trusts we identified 20 BRRA patients and 20 RA alone. BRRA patients had HRCT proven bronchiectasis without other lung disease and a history of ≥2 respiratory infections/year. RA patients had no respiratory symptoms, no respiratory disease and a normal CXR. All patients met the 2010 ACR/EULAR RA criteria. DAS28-CRP, serum RF(IgM) and ACPA(2 nd generation assay) were measured in all patients. Current disease modifying drugs, biologic drugs and hand and foot x-ray findings were recorded from clinical record review. Results: The groups were matched for RA disease duration, mean 12.9yrs BRRA group and 12.2yrs RA group. All components of DAS28-CRP except VAS were significantly higher in the BRRA group (Table 1 ). Autoantibody positivity in the BRRA group was significantly higher, 19 (95%) were positive for RF compared to 13 (65%) in the RA group (p=0.044) and 18 (90%) were positive for ACPA compared to 11 (55%) in the RA group (p=0.031). Where hand and foot x-rays were available, 9/15 BRRA (60%) and 6/15 (40%) RA had evidence of erosive change. There was no significant difference (p=0.75) in the proportion of patients on combination therapy with ≥ one disease modifying drug/biologic, 9/20 BRRA (45%) and 7/20 RA (35%). Conclusions: Patients with BRRA have higher DAS28-CRP and autoantibody positivity than those with RA alone. All components of DAS28-CRP, except the VAS (global) were significantly higher in the BRRA group demonstrating that the increase does not simply reflect higher CRP secondary to recurrent respiratory infections. Although numbers were too small to prove significance, an increased proportion of BRRA patients had erosive radiological change. Despite these findings DMARD/Biologic treatment was no more aggressive in the BRRA group suggesting under treatment of RA. It is likely this reflects concerns DMARD/Biologic treatment may exacerbate respiratory infections. There is currently no consensus on how to treat this challenging patient group, further studies are urgently required. References: McMahon et al. Bronchiectasis and rheumatoid arthritis a clinical study. Ann Rheum Dis 1993;52:776-779. Cortet et al. Pulmonary function tests and high resolution computed tomography of the lungs in patients with rheumatoid arthritis. Ann Rheum Dis 1997;56:596-600. Acknowledgements: Funding was by Arthritis Research UK. Research teams at the QE Gateshead, Freeman and Royal Cornwall Hospitals. Disclosure of Interest: None Declared